Imaging Tau Deposits In Vivo: Progress in Viewing More of The Proteopathy Picture - Mathis, Chester A.; Klunk, William E. (Neuron (Cambridge, Mass.), 2013)
In this issue of Neuron, Maruyama et al. (2013) demonstrate the binding of a new class of selective tau ligands, termed PBBs, to tau deposits in transgenic mice and in human subjects with normal cognition, Alzheimer’s disease, or a corticobasal syndrome.